PROBLEMS CAUSED BY DEFICIENCY IN MICRODRAINAGE IN THE CITY OF SANTO ANTÔNIO DE JESUS - BA - Caroline dos Santos Santana, Anna; Santos Silva, Lorena; Fonseca Couto, Carolina (Journal of Interdisciplinary Debates, 2022)
This study aims to evaluate the microdrainage system and how its deficiency impacts the shopkeepers and traffic in the Barros e Almeida Avenue in the city of Santo Antônio de Jesus - Bahia. A survey was conducted in order to identify the impacts caused by flooding and how they affect local businesses. Using flow rate calculations, it was determined that the number of existing manholes in the region is sufficient to meet the demand, however, their state of conservation and irregularities reduce their drainage capacity. It is understood that both citizens and public administration have responsibilities over the drainage system. This study points out how the lack of maintenance of the microdrainage system can be a potential adversity to businesses and commerce. Furthermore, the education of the population is important for its good functioning.